A theoretical model for curriculum implementation. - Common, Dianne. (University of Ottawa (Canada), 1978)
Many curriculum innovations introduced into schools have experienced implementation failure. From this seminal condition emerged a problem for investigation. There has been a dearth of information in the research literature on the problem of implementation, and conceptualization on the nature of this educational phenomenon is in a neophyte and disturbing state. Consequently education has a need for cogent and pervasive speculations relative to curriculum implementation. It is this need that gave rise to the purpose of the study---the formulation of a comprehensive, theoretical explanation for the process of curriculum implementation. The study did not engage in the production of empirical facts about implementation. Instead what was developed was a framework, or theoretical model, for making intelligible the facts already available. The central foundation or data base for the theoretical model was the descriptive data procured from twenty-five research studies on implementation. Additional evidence was drawn from numerous ancillary studies when further explication and elaboration was necessary to support or extend generalizations and categories emerging from the analysis of the central, descriptive data. The methodology was labelled as an interpretative-theoretical type. The methodology consisted of four fundamental, interdependent, sequenced but distinct phases. Phase one, or exploration, established the general purpose, research direction, and definitional limits of the study. The second phase was one of description. This phase required a descriptive, enumeration of twenty-five curriculum implementation studies. This, in turn, produced the foundational data base of the study. Phase three, or categorization, produced the essential and necessary categories of the curriculum implementation process. These categories emerged through abstractions and generalizations from the descriptive data base, and were supported and extended by additional evidence derived from ancillary implementation studies. The fourth stage of the study was the construction of a theoretical model that would represent the meaning of curriculum implementation. In order to accomplish this purpose, the theoretical model provided explications for the following research questions: (1) What are the component elements of curriculum implementation? (2) What is the purpose of curriculum implementation? (3) Who are the curriculum implementation actors? (4) How does implementation occur? The study concluded that the curriculum implementation process is composed of four necessary categories of essential elements; three elements of substance and one element of process. The three substantive categories were the curriculum, the user, and the organization. Each element was determined to have a particular characteristic nature relative to curriculum implementation, and each to have a particular function to perform in the process of realizing implementation goals. The process category was identified as one of planning. This was a planning process for action, or more specifically instructional action, and was characterized by the mutual interaction of the three categories of substantive curriculum implementation elements.
Keywords: Education, Curriculum and Instruction.